Analysis of Twins - Sonia R. Bhalotra; Damian Clarke (Institute of Labor Economics (IZA), 2022)
The occurrence of twin births has been widely used as a natural experiment. With a focus upon the use of twin births for identification of causal effects in economics, this chapter provides a critical review of methods and results.
Keywords: D10; I26; J13; J24; 330; twins; identification; fertility; birth spacing; child development; women's labour market outcomes; child penalty